2009
DOI: 10.1007/s10661-009-1216-y
|View full text |Cite
|
Sign up to set email alerts
|

Metal exposure and effects in voles and small birds near a mining haul road in Cape Krusenstern National Monument, Alaska

Abstract: Voles and small passerine birds were live-captured near the Delong Mountain Regional Transportation System (DMTS) haul road in Cape Krusenstern National Monument in northwest Alaska to assess metals exposure and sub-lethal biological effects. Similar numbers of animals were captured from a reference site in southern Cape Krusenstern National Monument for comparison. Histopathological examination of selected organs, and analysis of cadmium, lead, and zinc concentrations in liver and blood samples were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A 2007 risk assessment [3] assumed 100% bioavailability of a large suite of contaminants and concluded that the risks to a wide range of wildlife, plants and humans via ingestion and direct contact were to: 1) small mammals from elevated boron; 2) Willow Ptarmigan ( Lagopus lagopus ) from elevated Cd near the mine site (outside of CAKR); and 3) the cover of lichens and bryophytes out to 2,000 m from the haul road. Sublethal effects that could influence population numbers and health were not considered, however, and it is possible that the below-ground contaminant reservoir could contribute to these types of effects for a range of ecological receptors that live in or eat soil and vegetation and then introduce them into the broader food web [34]. Because of the early history of fugitive dust dispersion, the soil-based pool of contaminants could persist for many decades even if no further release of fugitive dusts occurred.…”
Section: Discussionmentioning
confidence: 99%
“…A 2007 risk assessment [3] assumed 100% bioavailability of a large suite of contaminants and concluded that the risks to a wide range of wildlife, plants and humans via ingestion and direct contact were to: 1) small mammals from elevated boron; 2) Willow Ptarmigan ( Lagopus lagopus ) from elevated Cd near the mine site (outside of CAKR); and 3) the cover of lichens and bryophytes out to 2,000 m from the haul road. Sublethal effects that could influence population numbers and health were not considered, however, and it is possible that the below-ground contaminant reservoir could contribute to these types of effects for a range of ecological receptors that live in or eat soil and vegetation and then introduce them into the broader food web [34]. Because of the early history of fugitive dust dispersion, the soil-based pool of contaminants could persist for many decades even if no further release of fugitive dusts occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The thrombotic and haemorrhagic lesions seen in the spinal cord in two lorikeets were severe and could have accounted for the signs observed and as a result these birds were removed from the study. Metastatic mineralization of soft tissues, a lesion seen in cadmium poisoned animals 16 and other aberrations of calcium, phosphorus and vitamin D homeostasis, was present in four lorikeets. Muscle haemorrhage (n = 1) and mild focal to focally extensive myodegeneration (n = 3) were seen.…”
Section: Resultsmentioning
confidence: 95%
“…1 In the current study, all but one of the lorikeets (n = 12) from RSPCA in 2017 were found to have evidence of recent exposure to cadmium. 16 But with the exception of a single lorikeet, the cadmium concentrations were not in the toxic range and would not have been expected to cause neuromuscular disease. Also, cadmium was not found to be significantly elevated in lorikeets from GVC and metastatic mineralisation was rare in all the lorikeets.…”
Section: Discussionmentioning
confidence: 99%
“…For each of the two DMTS road sites, four composite samples were obtained along a north-south transect; one each at distances of 25, 100, 200, or 300 m to the north of the road. At the New Heart Creek site, vegetation samples were obtained from one additional location slightly to the east of the transect line at a distance of 18 m from the road, which corresponded with the location where a vole was captured during a 2006 companion study (Brumbaugh et al 2010). Depending on availability, the four sub-locations used for creating each composite were located about 5 m to the north, south, east, and west of the transect point.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…In the spring of 2006, the U.S. Geological Survey, in cooperation with NPS researchers, devised a series of inter-related studies designed to address issues that were of a particular concern for natural resources within CAKR, and to develop strategies for future monitoring (Brumbaugh and May 2008;Brumbaugh et al 2010). One component of these studies was to document more recent metal concentrations, and to evaluate bioaccessibility of metals in vegetation.…”
Section: Introductionmentioning
confidence: 99%